Activity And Stability Test of Lip Balm Preparation Formulation from Ethanol Extract of Kersen Leaves (Muntingia calabura L.) As Sunscreen: Uji Aktivitas dan Stabilitas Formulasi Sediaan Lip Balm Ekstrak Etanol Daun Kersen (Muntingia calabura L.) sebagai Tabir Surya - More, Evanisia; Sui, Chendra Yunike; Rame, Magi Melia Tanggu (Universitas Airlangga, 2025)
Sunscreen was a cosmetic product that could chemically or physically inhibit the penetration of ultraviolet (UV) rays into the skin. One of the medicinal plants with notable sun protection properties was the leaf cherry (Muntingia calabura L.). The total flavonoid and phenolic content of cherry leaves possess unique antioxidants that helped protect the skin from damage caused by sun exposure. This study aimed to evaluate the stability and antioxidant activity of the lip balm extract from cherry leaves (Muntingia calabura L.) at concentrations of 0%, 4%, 6%, and 8%. This research employed an experimental design with four different concentrations: 0%, 4%, 6%, and 8%. Antioxidant testing was conducted using the DPPH method (2, 2-diphenyl-1-picrylhydrazyl), alongside sunscreen activity tests and stability assessments over 28 days at room temperature. The results from the antioxidant testing of the cherry leaf extract lip balm formulation indicated robust antioxidant activity, with an IC50 value showing that at a concentration of 4%, the initial value was 2.12 mg/L and the final value was 2.10 mg/L; at 6% concentration, the initial value was 1.11 mg/L and the final value was 1.13 mg/L; and at 8%, the values should be assessed. The ultra category SPF value was noted at a concentration of 8%, with an initial value of 45.93 and a final value of 33.69. Thus, it was concluded that the cherry leaf extract lip balm preparation had good antioxidant and SPF properties. Keywords: lip balm, cherry leaf extract, sunscreen